PENGARUH PENGGUNAAN MEDIA DAN LAMA WAKTU TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK LELE DUMBO: The Effect of Media Use And Length Of Time On The Physicochemical and Organoleptic Characteristics of Dumbo Catfish - Ahmad Mahda Vikia; Rosiana Ulfa; Arfiati Ulfa Utami (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2023)
Catfish is a type of freshwater fish that is most widely cultivated by people because it has a high nutritional content and is also easy to cultivate. Catfish easily experience a decline in quality caused by lipid oxidation, protein degradation, and also microbial contamination. One effort that can be made to maintain the shelf life of catfish is by smoking. Smooking is often carried out using various types of smoking media, including wood, coconut shells, coconut husks, and rice husks. However, it is not yet known how long the smoking time is appropriate to produce smoked catfish with good organoleptic and chemical qualities. Therefore, this research was conducted to determine the appropriate length of time for smoking catfish regarding organoleptic quality, water, and protein content. The research was conducted using a 2 Factor Completely Randomized Design, where the first factor was the type of media including wood (P1), coconut shell (P2), coconut husks (P3), and rice husks (P4), and the second factor was the length of time smoked. includes a smoking time of 2 hours (L2) and a smoking time of 3.5 hours (L3). The results showed that different smoking media treatments and smoking duration had a significant influence on the physicochemical and organoleptic properties of smoked African catfish at a fairly large level (p < 0.05). The best treatment is smoking using coconut shell media for 2 hours duration (P2L2) which has the highest protein content of 23.30% and has the best organoleptic quality of color, aroma, taste, and texture. Meanwhile, the water content of smoked catfish is 49.70-56.46%, where the water content obtained in this study does not exceed the threshold set by BSN, namely a maximum of 60%.